Mendukung Wisata Literasi Budaya melalui Peningkatan Mutu Souvenir - Cahyaningsih, Diyah Sukanti; Widayati, Sri; Mariani, Ana; Rosefamurti, Ameera Dinanti; Aristianti, Sagita Divani; Tutuko, Pindo (JAST : Jurnal Aplikasi Sains dan Teknologi, 2023)
This activity aims to develop the potential for cultural literacy tourism in Padepokan Panji Asmoro Bangun Kedungmonggo Hamlet, Karangpandan Village, District. Pakisaji, Malang Regency. The service focuses on increasing the ability to equip Padepokan as a tourism destination for mask culture literacy. This activity responds to the problem of lack of resources, one of which is to procure souvenirs in sufficient quantities to meet the demand of tourist groups (large group visits). The solution is to invite partners to discuss so that they can find a SWOT study of this destination. The main priority problem to be resolved is the availability of souvenirs and souvenir packaging. The service team conducted training and provided materials for making mask souvenirs with three variations, namely coloring media masks, refrigerator magnet masks, and masks in the form of brooches. Souvenir packaging is also an important part, mask souvenirs require packaging that maintains their durability and cleanliness, but still shows the face of the mask when displayed. The Service Team prepares packaging designs to meet the criteria, effective, ergonomic, easy to recognize, easy to carry, artistic value, and promotional value. This dedication has provided a solution by completing the needs of tourist destinations in the form of souvenirs with packaging designed complete with mask character stories.ABSTRAKKegiatan ini bertujuan untuk mengembangkan potensi wisata literasi budaya di Padepokan Panji Asmoro Bangun Dusun Kedungmonggo, Desa Karangpandan, Kec. Pakisaji, Kabupaten Malang. Pengabdian berfokus pada peningkatan kemampuan melengkapi Padepokan sebagai destinasi wisata literasi budaya topeng. Kegiatan ini merespon permasalahan kurangnya sumber daya, salah satunya untuk pengadaan souvenir dalam jumlah yang memadai dalam memenuhi permintaan kelompok wisatawan (kunjungan rombongan dalam jumlah besar). Solusi yang dilakukan dengan menghadirkan mitra untuk berdiskusi sehingga menemukan kajian SWOT dari destinasi ini. Permasalahan yang menjadi prioritas utama untuk diselesaikan adalah ketersediaan souvenir dan pengemasan souvenir. Tim pengabdi melakukan pelatihan dan penyediaan bahan pembuatan souvenir topeng dengan tiga variasi, yaitu topeng media mewarnai, topeng magnet kulkas dan topeng dalam bentuk bros. Kemasan souvenir juga menjadi bagian penting, souvenir topeng memerlukan pengemasan yang menjaga keawetan dan kebersihannya, namun masih nampak wajah topengnya saat dipajang. Tim Pengabdi menyusun desain kemasan untuk memenuhi kriteria, efektif, ergonomis, mudah dikenali, mudah dibawa, bernilai seni, dan bernilai promosi. Pengabdian ini telah memberikan solusi dengan melengkapi kebutuhan destinasi wisata berupa souvenir dengan kemasan yang didesain lengkap dengan cerita karakter topeng.